Remaining Visual Field and Preserved Subjective Visual Functioning Prevent Mental Distress in Patients with Visual Field Defects - Gall, Carolin; Broesel, Doreen; Sabel, Bernhard (Frontiers in Human Neuroscience, 2013)
Background: Patients with visual field defects after visual pathway lesion may experience reduced vision-related quality of life (vrQoL). It has not been clarified how vrQoL impairments contribute to vision-related mental distress. Methods: 108 subjects with visual field defects caused by optic neuropathies (age M=57.6; SD=13.7 years) answered the National Eye Institute Visual-Functioning Questionnaire (NEI-VFQ) for vrQoL and the SF-12 Short Form Health Survey for health-related quality of life (hrQoL). A ten item composite of NEI-VFQ “visual functioning” and five items of “mental health symptoms due to vision problems” were subjected to Rasch analysis. The test battery comprised static and High Resolution Perimetry (HRP). Regression and path analysis were used to investigate associations between QoL, mental distress and perimetry results. Results: A higher level of “visual functioning” was associated with monocular impairment and a larger remaining visual field compared to binocular impairment. Subjective “visual functioning” but not visual field parameters predicted “mental health symptoms due to vision problems” which was the only variable associated with the SF-12 mental component score. The SF-12 physical component score was less strongly associated with “mental health symptoms due to vision problems”. Here, reaction time in HRP and mean threshold in perimetry were additional significant variables. Path analysis revealed a significant path of remaining visual field via visual functioning on mental health. Conclusions: Subjective consequences of visual impairments in everyday life impact mental health rather than “objective” visual function loss as measured by perimetry. Since a higher extent of vrQoL was related to lower levels of mental distress, the maintenance of vrQoL could reduce and prevent mental distress due to vision problems. Patients with persisting visual field defects may benefit from neuropsychological rehabilitation and supportive therapies.